Answer:
(1 - 2n)^3 equals
(1 -2n) * (1 -2n) * (1 -2n)
Step-by-step explanation:
The answer would be C (P=T/2). This can be explained by examining the ratio. If you were to put in the answer of T = 12, then you would be looking for T/2 or 6, assuming we're giving them each half of the amount original held by grandmother.
Answer:
p - w = $25 OR w + $25 = p
Step-by-step explanation:
pencil = p
pen = w
p - w = $25 OR w + $25 = p
4/11 because it is divisible by seven
Answer:
The standard form of quadratic equation is ![x^2-16x-36=0](https://tex.z-dn.net/?f=x%5E2-16x-36%3D0)
The factored form of
is ![(x+2)(x-18)=0](https://tex.z-dn.net/?f=%28x%2B2%29%28x-18%29%3D0)
Step-by-step explanation:
Given equation ![x^2-6=16x+30](https://tex.z-dn.net/?f=x%5E2-6%3D16x%2B30)
We have to write in standard form and then factorize the given equation.
The standard form for a general quadratic equation is given as ![ax^2+bx+c=0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0)
Consider
Taking all terms to left side, we have,
![x^2-6-16x-30=0](https://tex.z-dn.net/?f=x%5E2-6-16x-30%3D0)
Adding like terms, we have,
![x^2-16x-36=0](https://tex.z-dn.net/?f=x%5E2-16x-36%3D0)
Now we will factorize it.
We will solve the quadratic equation
using middle term splitting method,
-16x can be written as -18x+2x
becomes
![\Rightarrow x^2-18x+2x-36=0](https://tex.z-dn.net/?f=%5CRightarrow%20x%5E2-18x%2B2x-36%3D0)
Taking x common from first two terms and 2 common from last two terms we have,
![\Rightarrow x(x-18)+2(x-18)=0](https://tex.z-dn.net/?f=%5CRightarrow%20x%28x-18%29%2B2%28x-18%29%3D0)
![\Rightarrow (x+2)(x-18)=0](https://tex.z-dn.net/?f=%5CRightarrow%20%28x%2B2%29%28x-18%29%3D0)
Thus, the factored form of
is ![(x+2)(x-18)=0](https://tex.z-dn.net/?f=%28x%2B2%29%28x-18%29%3D0)